DIRECTIVE ACTS IN ONWARD FILM BY DAN SCANLON - Zuhrotunnisa Elviana Indah Kumala; Zuliati Rohmah (Universitas Islam Negeri Sunan Gunung Djati, 2021)
This study aims to describe the types of directive acts contained in the Onward film using the theory of Keith Allan (1986). The subject of this study is the main characters of the Onward film by Dan Scanlon. This qualitative-descriptive study collected data from the main characters’ utterances of the film in the form of words, phrases, or sentences that contain directive acts in each scene of the Onward film. The researchers collected data by listening, recording, and note-taking to obtain complete and reliable data on various forms of directive acts. The researchers as the main instruments analyzed the data in four stages: identification, classification, interpretation, and conclusion. The results of the analysis of 51 directive acts show six kinds of directive acts, that is, advice, requirements, permissions, prohibitions, questions, and requests with questions as the most dominant ones. Keywords: Speech Acts, Directive Act, Film Dialogues, Onward Film